The wildcat (Felis silvestris) in the Lower Bug Region (southern Ukraine) - Igor Nakonechny; Nataliia Shvets (Theriologia Ukrainica)
The wildcat (Felis silvestris) is one of the least studied species of the European mammal fauna and an important conservation target in the Ukrainian network of protected areas. The increase in the number of records of the species in recent decades, including on the south-eastern border of its range, indicates the stabilisation of the western Ukrainian population and, at the same time, the potential for its dispersal from the Forest-Steppe to the Steppe. One of the latest sanctuaries of the species in the Lower Bug region is the territory of the Karmeliukove Podillia National Nature Park (20 203 ha). Observations of the wildcat in Trostianets and Chechelnytsia raions (Vinnytsia Oblast), which are part of the Park’s territory, have been recorded since 2009. In 2017–2024, these animals, their hiding places and traces of their life activity were detected annually in the Park’s forested areas and in the quarters of the Haisyn forestry enterprise. The reports of these institutions indicate that at least 30 individuals currently live in the forest-steppe interfluve of the Savranka, Kodyma, and Bug rivers, forming a stable centre of the species population, from which individuals are dispersing through the Bug eco-corridor to the territory of Mykolaiv Oblast. This process of dispersal into the steppe area of the Bug Lowlands is rather sporadic, but it has led to the species’ penetration far to the south-east, almost to the sea coast in the area of the Bug–Berezan interfluve. Since the autumn of 2017, periodic sightings of the species have been recorded there in the area between the villages of Kovalivka, Zelenyi Hai, and Stepove in Mykolaiv Raion. A cadastre of wildcat records in the Lower Bug region was created, which includes 21 locations; all these points are marked on a map. The reason for the increase in abundance and expansion of the geography of records is the increase in the population core in Podillia and the improvement of habitat conditions in the Bug region on the whole, including the Lower Bug, where the species has moved beyond the forest-steppe along riverine habitats and has actually penetrated the steppe zone. As a result, in 2017–2024, the number of sightings of the wildcat in the steppe Bug region increased by 5–7 registrations annually, indicating that the species dispersed from the river valleys of the Bug hydrosystem to adjacent areas of the agricultural landscape. According to the characteristics of the habitats occupied by wildcats, they are confined to balka and bairak forests and floodplain meadows near rivers.